2015
DOI: 10.1136/tobaccocontrol-2015-052508
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of smoke-free policies in seven cities in China, 2007-2012

Abstract: Background China is the world’s largest consumer of tobacco, with hundreds of millions of people exposed daily to secondhand smoke (SHS). Comprehensive smoke-free policies are the only effective way to protect the population from the harms of SHS. China does not have a comprehensive national smoke-free law but some local-level regulations have been implemented. Objective To evaluate local level smoke-free regulations across seven cities in China by measuring the prevalence of smoking in public places (workpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
4
18
0
Order By: Relevance
“…While smoking decreased in those cities that had implemented partial smoke-free laws between survey waves, there was no difference in the decrease in these cities compared with cities where no laws were implemented, demonstrating the failure of partial smoking bans to achieve even a partial reduction in SHS. These results are also consistent with previous research in China showing high levels of SHS exposure in public places—especially in rural areas—as well as no difference in SHS exposure in Chinese cities that had smoke-free restrictions in place compared with those without local smoke-free laws 10 13 29–31…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While smoking decreased in those cities that had implemented partial smoke-free laws between survey waves, there was no difference in the decrease in these cities compared with cities where no laws were implemented, demonstrating the failure of partial smoking bans to achieve even a partial reduction in SHS. These results are also consistent with previous research in China showing high levels of SHS exposure in public places—especially in rural areas—as well as no difference in SHS exposure in Chinese cities that had smoke-free restrictions in place compared with those without local smoke-free laws 10 13 29–31…”
Section: Discussionsupporting
confidence: 92%
“…Although studies have shown the weak impact of existing partial smoke-free laws across China and the need for stronger comprehensive laws,8–11 very little is known about the impact of current smoke-free policies in rural areas—where almost half (44%) of the Chinese population lives 12. Rural smoking rates have risen in recent years such that by 2015, male smokers in rural areas had a higher smoking prevalence, smoked more cigarettes per day and spent more of their income on cigarettes than urban smokers 13 14.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in hospitals and schools and to a lesser extent in hospitality venues like hotels and bars. These findings are similar to a study carried out in China, where the majority of the population supported the prohibition of smoking in schools and public vehicles (85%), in hospitals (73%) and in offices (58%) while only 17% supported prohibiting smoking in restaurants and 11% supported in bars 21 . Similar findings were observed in Poland where the respondents also favoured bans in workplaces, on public transportation and public buildings over bans in bars, pubs and cafes 22 .…”
Section: Discussionsupporting
confidence: 78%
“…In those venues, PM 2.5 levels were significantly greater than in non-smoking venues. As has been observed in Indonesia [20,21] and internationally [22,23,24], we found that non-enforcement of smoke-free laws fails to provide needed protection from SHS exposure for nonsmokers, including children. The PM 2.5 levels observed in this study were lower than those found in a 2009 convenience sample of 17 restaurants in Jakarta (~110 µg/m 3 ) [21] and in many similar venues sampled globally [16,25,26].…”
Section: Discussionsupporting
confidence: 64%